(untitled) (AYUSHDHARA, 2024)
Karna is an essential sensory organ associated with Shravana-hearing and is considered one of the Navadwaras, majorly influenced by the Akasha Mahabhuta. Acharya Sushruta has explained 28 ear diseases and Karnasrava is one among them. This article highlights the significance of local therapeutic interventions (Sthanika Chikitsopakramas) in the effective treatment of Karna Srava. A 34-year-old male patient visited the Shalakya Tantra Outpatient Department (OPD) at JJAMC, Aligarh, complaining of left ear pain for four days, along with itching. On examination, pus and fungal mass were found in the left ear canal and the tympanic membrane was not visible. The patient was treated using Karna Sthanika Chikitsopakramas, including Karna Prakshalana (ear irrigation) and Karna Dhupana (fumigation), along with Shaman aushadhis (internal medicines). These treatments resulted in complete recovery from the disease. The signs and symptoms seen in this case align with those of otomycosis, a fungal infection of the ear canal, which typically presents with pain, itching, discharge and ear blockage. Sincere immediate treatment of ear-related conditions is crucial due to the delicate nature of the ear and the importance of hearing. Early intervention helps to prevent complications and ensures early optimal recovery.